Factors Associated with Women’s Chronic Disease Management: Associations of Healthcare Frustrations, Physician Support, and Self-Care Needs - Matthew Lee Smith; Marcia G. Ory; SangNam Ahn; Toni P. Miles (Journal of Aging Research)
Previous research emphasizes the importance of reducing healthcare frustrations and enhancing physician supports to help patients engage in recommended healthcare regimens. However, less is known about how these factors are associated with aging women’s knowledge about self-care behavior. This study examined the sociodemographics, health indicators, healthcare-related frustrations, and perceptions of physician support associated with middle-aged and older adult females’ self-reported need for help to learn how to take better care of their health. Data were analyzed from 287 females with one or more chronic conditions who completed The National Council on Aging (NCOA) Chronic Care Survey. A logistic regression model was developed. Women who were non-White (OR=2.26, P=0.049) were more likely to need help learning how to better manage their health. Those who had some college education or more (OR=0.55, P=0.044) and lower healthcare-related frustrations (OR=0.44, P=0.017) and perceived to have more physician support (OR=0.49, P=0.033) were less likely to need help learning how to better manage their health. Findings can inform the planning, implementation, assessment, and dissemination of evidence-based self-management programs for middle-aged and older women within and outside of clinical settings.